Vaccine-Linked Chemotherapy Approach: Additive Effects of Combining the Listeria monocytogenes-Based Vaccine Lm3Dx_NcSAG1 With the Bumped Kinase Inhibitor BKI-1748 Against Neospora caninum Infection in Mice - Imhof, Dennis; Pownall, William Robert; Schlange, Carling; Monney, Camille; Ortega-Mora, Luis-Miguel; Ojo, Kayode K.; Van Voorhis, Wesley C.; Oevermann, Anna; Hemphill, Andrew (Frontiers in Veterinary Science, 2022)
The apicomplexan parasite Neospora (N.) caninum causes neosporosis in numerous host species. There is no marketed vaccine and no licensed drug for the prevention and/or treatment of neosporosis. Vaccine development against this parasite has encountered significant obstacles, probably due to pregnancy-induced immunomodulation hampering efficacy, which has stimulated the search for potential drug therapies that could be applied to limit the effects of neosporosis in dams as well as in offspring. We here investigated, in a pregnant neosporosis mouse model, the safety and efficacy of a combined vaccination-drug treatment approach. Mice were vaccinated intramuscularly with 1x107 CFU of our recently generated Listeria (L.) monocytogenes vaccine vector expressing the major N. caninum tachyzoite surface antigen NcSAG1 (Lm3Dx_SAG1). Following mating and experimental subcutaneous infection with 1x105 N. caninum (NcSpain-7) tachyzoites on day 7 of pregnancy, drug treatments were initiated using the bumped kinase inhibitor BKI-1748 at 20 mg/kg/day for 5 days. In parallel, other experimental groups were either just vaccinated or only treated. Dams and offspring were followed-up until day 25 post-partum, after which all mice were euthanized. None of the treatments induced adverse effects and neither of the treatments affected fertility or litter sizes. Cerebral infection in dams as assessed by real time PCR was significantly reduced in the vaccinated and BKI-1748 treated groups, but was not reduced significantly in the group receiving the combination. However, in non-pregnant mice, all three treatment groups exhibited significantly reduced parasite burdens. Both, vaccination as well BKI-1748 as single treatment increased pup survival to 44 and 48%, respectively, while the combination treatment led to survival of 86% of all pups. Vertical transmission in the combination group was 23% compared to 46% and 50% in the groups receiving only BKI-treatment or the vaccine, respectively. In the dams, IgG titers were significantly reduced in all treatment groups compared to the untreated control, while in non-pregnant mice, IgG titers were reduced only in the group receiving the vaccine. Overall, vaccine-linked chemotherapy was more efficacious than vaccination or drug treatment alone and should be considered for further evaluation in a more relevant experimental model.